EVALUASI KERENTANAN DAN KESIAPSIAGAAN MASYARAKAT DALAM MENGHADAPI BENCANA TANAH LONGSOR DI DESA BERUK TAHUN 2024 - Rizaldy Himy Sagito; Pipit Wijayanti; Gentur Adi Tjahjono (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2025)
EVALUATION OF COMMUNITY VULNERABILITY AND PREPAREDNESS IN FACING LANDSLIDE DISASTERS IN BERUK VILLAGE IN 2024 This study analyzes the vulnerability and preparedness of the community in Beruk Village in facing landslide disasters. Due to its hilly topography, the village is at risk of landslides every year, making it essential to enhance community preparedness to reduce disaster impacts and strengthen their resilience in emergency situations. This research adopts a quantitative approach using documentation and questionnaires involving 95 respondents from various hamlets. The data was analyzed spatially and descriptively, focusing on physical, social, economic, and environmental vulnerabilities. Preparedness was measured through indicators such as knowledge, policies, emergency response plans, early warning systems, and resource mobilization. The findings reveal that Pingkok Hamlet has a medium level of vulnerability, while other hamlets like Ngantirejo, Beruk Wetan, Beruk Kulon, and Kambangan have low vulnerability. In terms of preparedness, Ngantirejo, Kambangan, and Gunung Lading Hamlets are deemed relatively prepared, while Pingkok and Beruk Wetan fall under the category of "almost ready." Other hamlets, such as Beruk Kulon and Pringombo, are considered less prepared, and Selangkah Hamlet has shown no significant preparedness for disasters. Efforts to improve preparedness include disaster education, strengthening early warning systems, developing clear evacuation plans, and fostering greater collaboration between the government and the community. These efforts are expected to enhance the preparedness of Beruk Village against landslide disasters.